The ultraslow spreading Knipovich Ridge: Mechanisms of melt focusing and segmentation - Meier, Michaela; Schlindwein, Vera; Scholz, John-Robert; Geils, Jonah; Schmidt-Aursch, Mechita C.; Krüger, Frank; Czuba, Wojciech; Janik, Tomasz (2020)
Ultraslow spreading ridges form the slowest divergent plate boundaries on Earth. Their distinct spreading processes build volcanically active magmatic segments in between amagmatic segments that exhibit mantle rocks at the seafloor. Local seismicity studies along ultraslow spreading ridges are up to now limited in their extend and can only give insights into spreading processes of segment parts. With our new microseismicity dataset we extend the coverage to multiple segments allowing us to study spreading processes on the scale of entire segments. The network of ocean bottom seismometers consisted of 26 stations deployed for one year approximately 160 km along the Knipovich Ridge in the Greenland Sea. More than 8000 events were reliably located with HYPOSAT and they exhibit a varying seismicity pattern along the rift axis. Maximum earthquake hypocentres shallow over distances of 70 km towards the Logachev volcanic centre, where swarm activity occurs in an otherwise aseismic zone. The undulating brittle-ductile boundary might map the focusing of melt towards major volcanic centres along the parallel lithosphere-asthenosphere boundary. Numerous earthquake swarms close by the volcanic centre indicate its current activity. The absence of shallow seismicity in the upper 8 km underlain by a band of seismicity characterizes presumably melt-poor regions. Both boundaries of the seismicity band are supposedly temperature controlled. Aseismic zones may mark areas, where mantle rocks are altered and too weak to exhibit seismicity recorded by our network. One of the studied segments cannot be identified as magmatic or amagmatic, rather the reorientation of the ridge axis in this area and related changes in the stress regime might lead to a more complex seismicity pattern. Although detachment faults are expected along amagmatic spreading segments, we do not observe clear indication on this type of faulting. We observe a fine-scale segmentation of seismic activity similar to a stripe and gap pattern, where the seismicity band ...